The Evans Osteotomy without Fixation Does Not Increase the Nonunion Rate - Solangel Rodriguez Materon MD; Brian P. Gallagher MD; Megan Miles MD; Smitha E. Mathew MBBS; Nacime Salomao Barbachan Mansur MD, PhD; Amos Dai MD; Eslam Alkaramany MD; Gregory P. Guyton MD (Foot & Ankle Orthopaedics, 2024)
Category: Hindfoot; Other Introduction/Purpose: The Evans osteotomy is a lateral column lengthening procedure of the calcaneus that is commonly used in the correction of flexible flatfoot deformities. Currently, there is no consensus on whether fixation is necessary when performing this osteotomy. The primary aim of this study was to determine the nonunion rate of an unfixed Evans osteotomy with use of an allograft wedge performed in patients undergoing flexible flatfoot reconstruction. The secondary aim was to report on the incidence and magnitude of calcaneocuboid (CC) joint subluxation. Methods: a retrospective chart review was done for a consecutive series of 145 feet in 137 patients who underwent Evans osteotomy as part of a flatfoot reconstruction with allogenic bone graft between January 2013 and October 2017, by a single fellowship-trained foot and ankle surgeon. Of those, 118 cases were available for analysis at a mean follow up of 62.5 weeks (SD 56.9). No fixation was used in any case. Time to union, estimated by clinical and plane radiographic evaluation was recorded, along with standard measures of deformity correction and CC joint subluxation. Results: There was only one nonunion 1/118 (0.84%) at final follow up. The mean time to union was 10.9 weeks (SD 1.56). Postoperative calcaneocuboid joint subluxation occurred in 50.8% of feet, with a mean of 1.51 mm, SD 2.3 mm and no correlation with wedge size (r=0.05, p=0.55). The mean wedge size was 7.1 mm , SD 1.4 mm (range, 5-12 mm). There was no correlation between wedge size and change in lateral column length (r=0.13, p=0.16). There was significant change between pre and postoperative calcaneal pitch, talonavicular uncoverage percentage, anteroposterior and lateral talo-first metatarsal angle, medial and lateral column height, and lateral column length (p < 0.05). Conclusion: Evans osteotomy without fixation for symptomatic flatfoot deformity resulted in an exceptionally low nonunion rate. CC joint subluxation occurred frequently but was small in magnitude, a finding that may be related to the relatively small size of the wedges used.